2008
DOI: 10.1186/1472-6920-8-31
|View full text |Cite
|
Sign up to set email alerts
|

Consultant medical trainers, modernising medical careers (MMC) and the European time directive (EWTD): tensions and challenges in a changing medical education context

Abstract: Background: We analysed the learning and professional development narratives of Hospital Consultants training junior staff ('Consultant Trainers') in order to identify impediments to successful postgraduate medical training in the UK, in the context of Modernising Medical Careers (MMC) and the European Working Time Directive (EWTD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…Numerous European studies have demonstrated reduced continuity of care, involvement in patient care directly with faculty, exposure to high-quality operative education, and general discontent among faculty and trainees. [28][29][30][31][32][33][34] The experiential learning model has been used to formulate medical educator professional development curricula 35 and could similarly be used to refine surgical educational curricula. The pre- (Table 5) [36][37][38][39][40] ; generally, our results confirm these findings on a larger scale and for the first time compare surgical faculty with residents and students.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous European studies have demonstrated reduced continuity of care, involvement in patient care directly with faculty, exposure to high-quality operative education, and general discontent among faculty and trainees. [28][29][30][31][32][33][34] The experiential learning model has been used to formulate medical educator professional development curricula 35 and could similarly be used to refine surgical educational curricula. The pre- (Table 5) [36][37][38][39][40] ; generally, our results confirm these findings on a larger scale and for the first time compare surgical faculty with residents and students.…”
Section: Discussionmentioning
confidence: 99%
“…Staffing issues have recently come to the fore in UK hospitals with the introduction of the European Working Time Directive (Tsouroufli and Payne 2008). This legislation limits the number of hours a junior doctor is able to work in the hospital for health and safety reasons.…”
Section: Discussionmentioning
confidence: 99%
“…FT offers more structured and focused training that is less dependent on the formal clinical environment. However, postgraduate training is tested by the restrictions in hours and patterns of working resulting from the implementation of the European Working Time Directive (EWTD) 4 5. All these factors have the potential to reduce postgraduates' exposure to clinical activity, reduce close contact with senior doctors, and offer less opportunity to be part of complete patient episodes.…”
Section: Introductionmentioning
confidence: 99%